Pengaruh Komposisi Media Tanam Arang Sekam Dan Pupuk Kandang Domba Terhadap Pertumbuhan Sambung Pucuk Tanaman Avokad (Persea americana Mill) Varietas Sindangreret - Ai Suminarti Dewi; Hudaya Mulyana; Tien Turmuktini (OrchidAgro, 2021)
The experiment was carried out in Karangbungur Village, Buahdua, Sumedang at an altitude of 170 meters above sea level. The experiment was carried out from July to August 2020. The aim of the experiment was to determine and study the effect of the interaction between the composition of the husk charcoal growing media and sheep manure on the grafting growth of avocado (Persea americana Mill.) Sindangreret variety. The experimental design used was a factorial randomized block design (RBD) consisting of 2 factors and repeated 3 times. The first factor is husk charcoal (a) consisting of 3 levels, namely a0 (0 t ha-1) a1 (9 t ha-1) a2 (18 t ha-1). The second factor is sheep manure consisting of 3 levels, namely b0 (0 t ha-1) b1 (9 t ha-1) b2 (18 t ha-1). The results showed that there was an interaction with root volume and no interaction with shoot emergence time, shoot length (4, 5, 6, 7, and 8 weeks after connection), number of leaves (6, 7, and 8 weeks after connection), and the percentage of live connections.